A double stator permanent magnet generator integrated with novel magnetic gear - Salihu, Mustafa Shehu; Misron, Norhisam; Othman, Mohammad Lutfi; Mariun, Norman; Hanamoto, Tsuyoshi (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
This paper presents a double stator Permanent Magnet (PM) generator integrated with a novel magnetic gear structure which is proposed to be used as a direct drive generator for low speed applications. Torque transmission is based on three rotors consisting of prime permanent-magnet (PM) poles in the middle rotor and field PM poles in the inner and outer rotors respectively. The proposed machine combines the function of magnetic gearing and electrical power generation. The operating principle of the generator is discussed and its performance characteristics are analyzed using 2-D Finite-Element Method (FEM). Analysis results about its magnetic gear ratio, electrical power output, transmission torque and cogging torque are reported. Simulation results are in good agreement with the theoretical analysis of the proposed machine design.